2011
DOI: 10.1103/physreve.84.031927
|View full text |Cite
|
Sign up to set email alerts
|

Cell sorting based on motility differences

Abstract: Self-propelled particles are used to simulate cell aggregates in a model considering homogeneous adhesion forces between cells and using only motility differences as segregation drivers. The tendency of cells to follow their neighbors is also included in the formulation. Three model variants are explored, and the conditions on which motility differences may produce segregation are mapped in parameter diagrams. The evolution of the order parameter measuring cell segregation is similar to those found by models b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 21 publications
7
52
2
Order By: Relevance
“…The average of g i over all cells is the interface index g, which is a common measure for the degree of segregation in the system [7,14,15,26]. When g % 0 the two types of cells are completely segregated.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The average of g i over all cells is the interface index g, which is a common measure for the degree of segregation in the system [7,14,15,26]. When g % 0 the two types of cells are completely segregated.…”
Section: The Modelmentioning
confidence: 99%
“…Current models of sorting assume some physical difference between cell types-either in the form of adhesion [12], cortical tension [3,13] or motility [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have found that segregation is characterized by algebraic scaling laws and introducing even a moderate amount of local coherent motion will considerably speed up the segregation process (Figure 8). A variant of this computational model is published by Beatrici et al (2011) investigating the segregation of self-propelled particles in 2 dimensions, driven by differences only in motility but not in adhesion. In this model, the faster cells envelope the slower cells forming islands as segregation proceeds.…”
Section: Segregation By Collective Motion and Adhesionmentioning
confidence: 99%
“…First, referred to here as ''differential adhesivity'', is a variant of the classic differential adhesion hypothesis that reflects relative differences in cell-cell adhesion/interfacial tensions between different cell types that make specific cell-cell arrangements more energetically favorable (4,5). The second hypothesis is known as ''differential motility'', and reflects relative differences in the active motion of endodermal and ectodermal cells during sorting (6,7). Before now, there have been data to support both hypotheses in Hydra and other, related sorting systems (3).…”
mentioning
confidence: 99%